Enhanced Clearance of Neurotoxic Misfolded Proteins by the Natural Compound Berberine and Its Derivatives - Paola Rusmini (International Journal of Molecular Sciences, 2020)
Background: Accumulation of misfolded proteins is a common hallmark of several neurodegenerative disorders (NDs) which results from a failure or an impairment of the protein quality control (PQC) system. The PQC system is composed by chaperones and the degradative systems (proteasome and autophagy). Mutant proteins that misfold are potentially neurotoxic, thus strategies aimed at preventing their aggregation or at enhancing their clearance are emerging as interesting therapeutic targets for NDs. Methods: We tested the natural alkaloid berberine (BBR) and some derivatives for their capability to enhance misfolded protein clearance in cell models of NDs, evaluating which degradative pathway mediates their action. Results: We found that both BBR and its semisynthetic derivatives promote degradation of mutant androgen receptor (ARpolyQ) causative of spinal and bulbar muscular atrophy, acting mainly via proteasome and preventing ARpolyQ aggregation. Overlapping effects were observed on other misfolded proteins causative of amyotrophic lateral sclerosis, frontotemporal-lobar degeneration or Huntington disease, but with selective and specific action against each different mutant protein. Conclusions: BBR and its analogues induce the clearance of misfolded proteins responsible for NDs, representing potential therapeutic tools to counteract these fatal disorders.